Profiling of Nutrition, Essential Oil, and Antioxidant Capacity (IC50) of Lomo (Protium Javanicum Burm. F.) - Yanti, Sahri; Afgani, Chairul Anam; Suharli, Lili (Indonesian Food Science and Technology Journal, 2026)
Lomo (Protium javanicum Burm. F.) is an aromatic leaf traditionally used by the Samawa ethnic group in several local cuisines of Sumbawa, West Nusa Tenggara (NTB), Indonesia. In addition to its culinary applications, lomo has been reported to possess medicinal potential, including antitussive, gastroprotective, anti-inflammatory, antidiarrheal, anticancer, and antibacterial activities. This study aimed to determine the nutritional composition, identify functional groups, characterize the essential oil constituents, and evaluate the antioxidant capacity (IC₅₀) of lomo. Lomo samples were collected from Sumbawa, NTB. Essential oil composition was analyzed using gas chromatography–mass spectrometry (GC–MS). Proximate analysis revealed that lomo contained moisture (10.662%), ash (6.185%), protein (10.662%), fat (0.872%), and carbohydrates (71.619%). Functional group characterization using Fourier transform infrared (FTIR) spectroscopy indicated the presence of O–H, C=C–H, C=O, C–H, C–N, and C–O vibrational bonds. GC–MS analysis showed that the essential oil of lomo is a complex mixture comprising 189 compounds, which can be classified into terpene, sterol, fatty acid, cyclic ester, ether, alkenyne, and phenolic groups. The antioxidant capacity (IC₅₀) of lomo extracts was 9.043 mg/mL in moisture, 1367.053 mg/mL in n-hexane, and 5.800 mg/mL in methanol. The findings of this study provide baseline scientific information on the nutritional profile, functional groups, essential oil composition, and antioxidant activity of lomo. This information may support the development and diversification of herbal food and beverage products incorporating lomo, as well as contribute to the promotion of traditional Sumbawa culinary products such as sepat samawa and singang samawa.